Jawabanmu

2014-08-17T19:09:06+07:00
sin²x = 1 - cos²x selanjutnya
begini mungkin soalnya (sin²x + tan²x)
                                       
                                        2
= 2(sin²x + tan²x)
           x²
= 2(sin²xcos²x + sin²x)
            x²cos²x
= 2(sin²x(cos²x + 1))
          x²cos²x
= 2(1 - cos²x)(cos²x + 1)
             x²cos²x
= -2(cos²x - 1)(cos²x + 1)
               x²cos²x
= -2(cos²xcos²x - 1)
           x²cos²x
= 2 - 2cos²xcos²x               atau
        x²cos²x               
= 2 per x²cos²x     -  2cos²x per x²